Capacitance of Gated GaAs/AlGaAs Heterostructures Subject to In-plane Magnetic Fields - Jungwirth, T; Smrcka, L (1995)
A detailed analysis of the capacitance of gated GaAs/AlGaAs heterostructures is presented. The nonlinear dependence of the capacitance on the gate voltage and in-plane magnetic field is discussed together with the capacitance quantum steps connected with a population of higher 2D gas subbands. The results of full self-consistent numerical calculations are compared to recent experimental data.